Nilai Toleransi dan Hasil Belajar Siswa Melalui Pembelajaran Berbasis Masalah Berbasis Kearifan Lokal Appatabe' - Iis Inriani; Syarifuddin Cn Sida; Muhammad Nawir (Universitas Pendidikan Mandalika, 2022)
The study aims to analyze the influence of the Local Wisdom-based Problem Based Learning model Appatabe' on the value of tolerance and learning outcomes of the students of SD Inpres Hombes Armed Gowa Regency. This research method was quantitative research. This method of research was a quasi-experimental (quasi-experimental). The population in this study were all students of the Inpres Hombes Armed Elementary School, for the 2020/2021 Academic Year. The samples in this study were 32 students of Class Va as an experimental class and class Vb as a control class of 31 students of SD Inpres Hombes Armed. The instrument used was the value of tolerance, and social studies learning outcomes. The data analysis technique used is the data normality test, homogeneity test and hypothesis testing. The test results showed that from the results of the independent sample t-test with a significant value of 0.000 <0.05, this means that Ho is rejected, and Ha is accepted, meaning that there is a significant influence between tolerance and student learning outcomes in class V SD Inpres Hombes Armed. Thus, the Problem Based Learning Model Based on Local Wisdom Appatabe' affects the value of tolerance and student learning outcomes. Teachers can use this model in teaching and learning activities or create a new learning atmosphere.